PENGATURAN TALAK DAN ‘IDDAH (STUDI KOMPARATIF PRESPEKTIF FIKIH EMPAT MAZHAB DAN KOMPILASI HUKUM ISLAM (KHI)) - Hayati, Zakiyah (UIN Fatmawati Sukarno Bengkulu, 2017)
A happy family is born and the inner desire of each partner and the individuals who are in a family. But do not rule out the cherished goal, covenants they make together experiencing the shock impacting on the creation of the marital discord, disagreement, each party still carries each ego respectively. Therefore the happy marriage which was originally going to be cracks or divorce. With the divorce, the consequences are ‘Iddah. In the case of divorce and ‘Iddah arrangement was stipulated in Islamic law either globally or specifically (the four schools of jurisprudence) and Islamic Law Compilation (KHI).The problems of this study was twofold: 1. How do the provisions of divorce and ‘Iddah according to the four schools of fiqh and Islamic Law Compilation (KHI)? 2. How Relevance provisions of divorce and ‘Iddah according to the four schools of fiqh and Islamic Law Compilation (KHI) In the era of modern society ?.The method used in this compiler is a comparative descriptive method that describes the view of the four schools of jurisprudence about the divorce arrangements and ‘Iddah then linked to Islamic Law Compilation (KHI) in Indonesia. Type of research is the research library (library research), whereas the approach used in this study is a normative approach. In analyzing the data compiler using the deductive method with deductive mindset is to analyze the problem of divorce and ‘Iddah in general and then withdrawn on dissent in the Four Schools of Jurisprudence about the divorce arrangements and ‘Iddah.From the analysis that has been done in this study setting divorce and ‘Iddah contained in Jurisprudence four schools and Islamic Law Compilation (KHI) do not have much difference, and with the relevance of Jurisprudence four schools and Islamic Law Compilation (KHI) portion of provisions divorce and ‘Iddah that has prevailed still be valid in the era of modern society